Баграш-Бигра: СПК "Первый май" и история деревень, входящих в него / Ю. П. Басков, А. Я. Матвеев - Басков Юрий Петрович (Удмуртия, 2005)
Экземпляры: Ч/з (20160329) / Инвентарный номер: 103903 / Цена: 50.00 / Авт.знак: Б 27 / ГРНТИ: 03 / ББК: 63.3(2Рос.Удм)